Aripiprazole: from pharmacological profile to clinical use - Di Sciascio G (Dove Medical Press, 2015)
Guido Di Sciascio,1 Marco Andrea Riva21Department of Psychiatry, University Hospital “Policlinico”, Bari, Italy; 2Department of Pharmacological and Biomolecular Sciences, University of Milan, Milan, ItalyAbstract: Clinical experience with aripiprazole has confirmed the effectiveness and the safety of this novel antipsychotic drug in patients with schizophrenia as well as for the treatment of mania in type I bipolar disorder. However the generalization of the results from clinical trials requires further effort in order to address some issues and to overcome incorrect and partial interpretation of the clinical evidence. This article provides some straightforward guidance that may help clinical psychiatrists to translate the mechanism of action of aripiprazole into clinical setting, thus improving the appropriate use of the drug through rational application of its pharmacological profile. Examples of paradigmatic clinical situations are presented and discussed, suggesting possible intervention strategies, which may contribute to achieving the most appropriate use of the pharmacological properties of aripiprazole in real life settings.Keywords: partial agonist, dopamine receptor, antipsychotic switch, neuronal plasticity